Abortion Rights in the European Union : The EU’s Role in Protecting Access to Safe and Legal Abortions - Ekholm, Karolina (My University, 2023)
The right to have an abortion is universally debated subject with strong opinions on both sides of the argument. Abortion laws are becoming less restrictive across the globe, especially in the European Union (EU) where the Member State’s abortion laws are the most liberal in international comparison. However, the Constitutional Tribunal of Poland made a ruling in 2020 that created a near total ban on abortions in Poland which showcases that abortion is not a guaranteed right within the EU. The ruling has been condemned by the European Parliament and several human rights organs and organisations. This raises the question of how abortion is related to human rights and whether this affects the EU and its role in safeguarding human rights within the Member States. This thesis explores if and how abortion is implemented in EU law and how the EU can affect abortion access. The research revolves around abortion from the perspective of international human rights law, and whether abortion is related to human rights, in what capacity, and how that affects the EU. So far, the EU has avoided taking a legal stance on abortion, leaving abortion legislation to the Member States by concluding that abortion falls outside the scope of EU competence. Abortion is related to several human rights, among them the right to life and the right to privacy. One of the fundamental values of the EU is the respect for human rights. When abortion is defined as a human right the EU could start proceedings against Member States that infringe on abortion access to protect abortion access within the EU.
Keywords: abortion, human rights, fundamental values, EU competence, EU law